A review of lead contamination in South American birds: The need for more research and policy changes - Plaza, Pablo (2018)
Lead contamination is a worldwide problem that affects the health of several bird species and can cause biodiversity loss. However, in South America there is little information about this problem and the species affected. The aim of this study is to compile existing knowledge about lead contamination in South American bird species and propose actions to mitigate this problem. Through a literature search, we found 39 scientific articles on this topic studying 68 bird species. Most studies came from Argentina and Brazil (71.7%), but also from Chile (7.7%), Venezuela (7.7%), Colombia (5.1%), Bolivia (2.6%), Ecuador (2.6%) and Peru (2.6%). Almost all the articles were published between 2001 and 2017. Waterbirds and birds of prey were the avian guilds more studied. Seventy percent of the studies show individuals with lead concentrations that exceed established thresholds levels. The few available articles suggest that lead contamination may be a continental-scale problem produced by different sources like fuels, mining, industries and hunting ammunition. However, lead ammunition seems to be an underestimated source of lead which is producing the highest toxic levels in bird species from South America. To our knowledge, there are regulations about different lead sources but not for lead ammunition in any country, except for some regions in Argentina. The progressive banning of lead from all sources and particularly from hunting ammunition is the main and most effective way to reduce the risk for wildlife. Current obstacles must be overcome through a combined effort of governments, wildlife managers and local communities.